2016
DOI: 10.1155/2016/1083208
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Variation during the Menstrual Cycle in Women with Menstrual Pain

Abstract: Objective. This study is performed to obtain objective diagnostic indicators associated with menstrual pain using pulse wave analysis. Methods. Using a pulse diagnostic device, we measured the pulse waves of 541 women aged between 19 and 30 years, placed in either an experimental group with menstrual pain (n = 329) or a control group with little or no menstrual pain (n = 212). Measurements were taken during both the menstrual and nonmenstrual periods, and comparative analysis was performed. Results. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Each pulse profile provides information about the physiological conditions or disorders in the human body [5]. For example, Jeon et al studied pulse wave variation during the menstrual cycle and reported that the pulse appeared to be either string-like or slippery and rapid [6].…”
Section: Introductionmentioning
confidence: 99%
“…Each pulse profile provides information about the physiological conditions or disorders in the human body [5]. For example, Jeon et al studied pulse wave variation during the menstrual cycle and reported that the pulse appeared to be either string-like or slippery and rapid [6].…”
Section: Introductionmentioning
confidence: 99%
“…In According to Cholifah (2015), yoga that is done regularly has an impact on increasing b-endorphins up to 5 times. The initial process of yoga is to focus on controlling the breath while inhaling, relaxing the muscles, causing pain, and diverting it to exhale slowly between the noses (Doina, 2013;Doulatabad, S., 2013;Aprilyadi, N., 2018;Jeon, SH., 2016). Feelings of comfort will activate the hypothalamus to release endorphins which have a natural sedative effect (natural painkillers), thereby spreading a sense of comfort (Nivethitha, 2016;Talib, 2019;Hapsari, 2020;Arini, D., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…e analysis of the radial pulse waves is regarded as an important approach to evaluate patient status in traditional Chinese medicine (TCM) [1][2][3]. GUAN is a segment of the radial artery above the radial styloid process and a critical position for collecting pulse wave correctly in TCM diagnosis [4][5][6][7][8]. However, current methods for locating GUAN, including tactile sense and pressure sensor array, could not achieve precise positioning [5,6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…GUAN is a segment of the radial artery above the radial styloid process and a critical position for collecting pulse wave correctly in TCM diagnosis [4][5][6][7][8]. However, current methods for locating GUAN, including tactile sense and pressure sensor array, could not achieve precise positioning [5,6,[9][10][11][12][13]. When sizes of those single sensors are almost less than 10 mm × 10 mm, it is difficult for people to place sensitive areas of a single sensor at the center of GUAN each time by tactile sense [4,7,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%